Public-Private Partnership To Increase Economic Growth of Tourism Sector - Fafurida Fafurida; Izzatun Ni’mah (Muhammadiyah University Press, 2017)
The performance of the tourism sector in Kedungsepur region increases significantly viewed from the indicators of the number of tourism objects, labors, tourists, income, and the Gross Regional Domestic Product (GRDP) of the tourism sector, but the contribution of the tourism sector to the GRDP and the average of the tourists’ length of stay decreases. This shows that the performance of the tourism sector in Kedungsepur region decreases and the Public Private Partnership has not been optimallee implemented. Therefore, the researchers use the analysis of SWOT and AHP to find the strategy alternatives to increase the performance indicators of the tourism sector. The research result of the SWOT analysis shows that the development of tourism sector in Kedungsepur region is at the quadrant III, which supports the Turn Arround strategy by applyinga strategy formulated in the matrix of SWOT. And the research result based on the AHP analysis shows the priority based on the criteria of aspects and alternatives. The aspect of institutional and the Alternative strengthen the institutional internal relationship to be a priority in the development of tourism sector in Kedungsepur region.